Understanding the burden of focal epilepsy as a function of seizure frequency in the United States, Europe, and Brazil. Issue 2 (27th March 2017) - Gupta, Shaloo; Ryvlin, Philippe; Faught, Edward; Song, Wan T.; Kwan, Patrick
Summary: Objective: To understand the current burden of focal epilepsy (FE) as a function of seizure frequency. Methods: Patients were identified from the United States (2011, 2012, and 2013), five European countries (EU; France, Germany, Italy, Spain, United Kingdom) (2011 and 2013), and Brazil (2011 and 2012) National Health and Wellness Survey (NHWS), a nationally representative, Internet‐based survey of adults (18+ years). The NHWS collected data on respondents' quality of life (QoL), health utilities, productivity loss, and healthcare resource utilization. Indirect and direct costs were calculated from the literature. Altogether, 345 of 176, 093 (U.S.A.), 73 of 30, 000 (United Kingdom), 53 of 30, 001 (Germany), 53 of 30, 000 (France), 41 of 12, 011 (Spain), 37 of 17, 500 (Italy), and 71 of 24, 000 (Brazil) respondents self‐reported a diagnosis of FE. Results: Many respondents (U.S.A.: 56.2%; 5EU: 41.6%; Brazil + 5EU: 40.5%) reported persistent seizures (≥1 per year). Over 60% to just over 71% of respondents with FE were treated with antiepileptic drugs (AEDs). In the United States, seizure frequency was associated with hospitalizations, indirect costs (ages 18–60), and total direct costs. For the 5EU and Brazil + 5EU, seizure frequency was associated with physical QoL, health utilities, activity impairment, and emergency room (ER) visits. Additional associations were observed for the 5EU on hospitalizations, indirect costs (ages 18–60), ER visit costs, and total direct costs and for Brazil + 5EU on absenteeism, overall work impairment, and provider visits. Costing was not performed for Brazil + 5EU. Significance: Around half of the patients had persistent seizures despite most taking an AED in this 2011–2013 dataset. The results support the hypothesis that reducing seizures can improve productivity and reduce resource utilization and associated costs. Regional differences may reflect differences in healthcare systems and selected patient populations. Overall, the results suggest that additional treatment options are needed to improve seizure control and reduce related costs.